Polyamine Depletion Enhances The Roscovitine-Induced Apoptosis Through The Activation Of Mitochondria In HCT116 Colon Carcinoma Cells - Çoker, Ajda; Palavan Ünsal, Narçin; ARISAN, ELİF DAMLA (Springer, 233 Spring St, New York, Ny 10013 Usa, 2012)
Small molecule inhibitors of cyclin-dependent kinases (CDKs) show high therapeutic potential in various cancer types which are characterized by the accumulation of transformed cells due to impaired apoptotic machinery. Roscovitine, a CDK inhibitor showed to be a potent apoptotic inducer in several cancer cells. Polyamines, putrescine, spermidine and spermine, are biogenic amines involved in many cellular processes, including apoptosis. In this study, we explored the potential role of polyamines in roscovitine-induced apoptosis in HCT116 colon cancer cells. Roscovitine induced apoptosis by activating mitochondrial pathway caspases and modulating the expression of Bcl-2 family members. Depletion of polyamines by treatment with difluoromethylornithine (DFMO) increased roscovitine-induced apoptosis. Transient silencing of ornithine decarboxylase, polyamine biosynthesis enzyme and special target of DFMO also increased roscovitine-induced apoptosis in HCT116 cells. Interestingly, additional putrescine treatment was found pro-apoptotic due to the presence of non-functional ornithine decarboxylase (ODC). Finally, roscovitine altered polyamine catabolic pathway and led to decrease in putrescine and spermidine levels. Therefore, the metabolic regulation of polyamines may dictate the power of roscovitine induced apoptotic responses in HCT116 colon cancer cells.
Keywords: polyamines; apoptosis; roscovitine; DFMO; colon carcinoma; cyclin-dependent kinase; breast-cancer cells; lymphocytic-leukemia cells; r-roscovitine; inhibitor roscovitine; cdk inhibitor; s-phase; b-cll; combination; seliciclib; poliaminler; kolon karsinoması; siklin bağımlı kinaz; göğüs kanseri hücreleri; lenfositik lösemi hücreleri; kombinasyon